2000
DOI: 10.1038/35007085
|View full text |Cite
|
Sign up to set email alerts
|

PAR3 is a cofactor for PAR4 activation by thrombin

Abstract: Identification of the mechanisms by which the coagulation protease thrombin activates platelets is critical for understanding haemostasis and thrombosis. Thrombin activates cells at least in part by cleaving protease-activated G-protein-coupled receptors (PARs). PAR3 and PAR4 are thrombin receptors expressed in mouse platelets. Inhibition of thrombin binding to mPAR3 (ref. 4) and knockout of the mPAR3 gene inhibited mouse platelet activation at low but not high concentrations of thrombin. Thus PAR3 is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
490
3
5

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(513 citation statements)
references
References 24 publications
15
490
3
5
Order By: Relevance
“…Although subtypes of thrombin-responsive PARs, PAR-1, PAR-3, and PAR-4, are present and functionally active in VSMCs, PAR-1 has the highest affinity for thrombin [31] . PAR-1 is the prototypic thrombin receptor and the main isoform involved in VSMC neointimal formation and restenosis in vivo [32] , whereas PAR-3 appears to function as a cofactor for PAR-4 [33] . In this study, we found that a PAR-1 antagonist (SCH79797) significantly inhibited thrombin-induced CTGF expression, while a PAR-4 antagonist (tcY-NH 2 ) had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Although subtypes of thrombin-responsive PARs, PAR-1, PAR-3, and PAR-4, are present and functionally active in VSMCs, PAR-1 has the highest affinity for thrombin [31] . PAR-1 is the prototypic thrombin receptor and the main isoform involved in VSMC neointimal formation and restenosis in vivo [32] , whereas PAR-3 appears to function as a cofactor for PAR-4 [33] . In this study, we found that a PAR-1 antagonist (SCH79797) significantly inhibited thrombin-induced CTGF expression, while a PAR-4 antagonist (tcY-NH 2 ) had no effect.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about PAR 3 since in cells transfected with this receptor, no intracellular signal transduction has been detected in response to either thrombin or its tethered ligand peptide [9]. Interestingly, one study showed the implication of PAR 3 as an accessory protein binding thrombin by its hirudin-like domain for PAR 4 activation [10]. Like PAR 4 was the most recent member of the PARs family to be cloned, very little is known about the physiological and pathophysiological importance of this receptor in visceral pain.…”
Section: Protease-activated Receptors: Structure and Activationmentioning
confidence: 99%
“…There are currently three active members of the PAR family, PAR 1, 2 and 4 (Bohm et al, 1996;Ishihara et al, 1997;Vu et al, 1991;Kahn et al, 1998;Xu et al, 1998). Family member, PAR 3 , has been found to be a co-factor for PAR 4 and as such may not be considered as an active receptor in its own right (Nakanishi-Matsui et al, 2000). Interestingly, peptides corresponding to the ®rst ®ve to six amino acids of the tethered ligand will activate these receptors independently of proteolysis.…”
Section: Introductionmentioning
confidence: 99%